Fathers’ Involvement in Parenting and Intimacy towards Husbands - Diana Savitri Hidayati; Christal Nandya Deby Mayang Sari (Jurnal Perempuan dan Anak, 2020)
Each marriage must have a problem, no exception to the newly married couple. Individuals who have intimacy in their marriage will be easier to deal with the conflicts that occur with their partner. One of the things that allegedly caused women's difficulties to bring intimacy to her husband was the woman's relationship with past experiences that were closely related to parental care, especially dad. The purpose of this research is to know the relationship of father involvement in parenting with intimacy to husbands. The research design used is quantitative correlational. The Instrument for measuring both variables in the study uses the father's involvement scale in parenting and the intimacy scale. The research location is in a sub-district in Malang Regency with the number of subjects 99 wife and sampling techniques using purposive sampling. The research subject criteria are: aged between 18- 25 years old, taken care of by father until 18 years old, not going through long distance relationship with her husband, minimum 1 year marriage and minimum number of children is one person. Data analysis using product moment. The results showed that there was a significant positive relationship between the involvement of the father in the care of intimacy against the husband with the value of coefficiencies R = 0.397, with significance p = 0.000 < 0.05.